IEEE Symposium Conference Record Nuclear Science 2004.
DOI: 10.1109/nssmic.2004.1462181
|View full text |Cite
|
Sign up to set email alerts
|

Thermal neutron backscatter imaging

Abstract: Objects of various shapes, with some appreciable hydrogen content, were exposed to fast neutrons from a pulsed: D-T generator, resulting in a partially-moderated spectrum of backscattered neutrons. The thermal component of the backscatter was used to form images of the objects by means of a coded aperture thermal neutron imaging system. Timing signals; from the neutron generator were used to gate the detection system so as to record only events consistent with thermal neutrons traveling the distance between th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
8
0

Publication Types

Select...
3
2

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(9 citation statements)
references
References 5 publications
0
8
0
Order By: Relevance
“…Coded aperture imaging of thermal neutron sources has previously been proposed for a number of applications, including warhead counting for treaty verification [1], detecting nuclear smuggling [2], explosives detection [3,4], monitoring stored spent nuclear fuel [5]. In earlier testing of our coded aperture camera, which uses a 2-dimensional He-3 positionsensitive wire chamber and a Cd mask, we used isotopic sources (such as 252 Cf or 241 Am-Be) which continuously emitted fast neutrons that were then thermalized in paraffin.…”
Section: Prior Workmentioning
confidence: 99%
See 4 more Smart Citations
“…Coded aperture imaging of thermal neutron sources has previously been proposed for a number of applications, including warhead counting for treaty verification [1], detecting nuclear smuggling [2], explosives detection [3,4], monitoring stored spent nuclear fuel [5]. In earlier testing of our coded aperture camera, which uses a 2-dimensional He-3 positionsensitive wire chamber and a Cd mask, we used isotopic sources (such as 252 Cf or 241 Am-Be) which continuously emitted fast neutrons that were then thermalized in paraffin.…”
Section: Prior Workmentioning
confidence: 99%
“…We also showed that the imager could be operated in a gated mode in combination with a D-T neutron generator to produce images of hydrogenous materials (simulating explosives). In that case [3], the time gate for the data acquisition was chosen to reduce the response of the He-3 chamber to neutrons with energies above the 1-eV absorption threshold of the Cd mask. Such epithermal neutrons travel about 1.4 meters in 100 s or less, and can be detected by 3 He with an efficiency of a few percent.…”
Section: Prior Workmentioning
confidence: 99%
See 3 more Smart Citations